Aspectos clínicos e nutricionais do recém-nascido de baixo peso no método-canguru: uma revisão integrativa - VILHENA, Amanda Rodrigues de (2024)
Objective: To identify clinical and nutritional aspects of low birth weight newborns in the kangaroo care method in the scientific literature. Methods: Integrative review of the literature carried out in June and July 2023, using the databases: Virtual Health Library (VHL), and CAPES Periodical, through the descriptors in Health Sciences (DeCS): Kangaroo method, Newborn of low weight and breastfeeding. Results: Based on the descriptors, 73 articles were found in the databases; After that, the titles and abstracts that met the inclusion and exclusion criteria were selected, totaling 8 articles to compose the review. Final considerations: From this study, the fundamental role of the multidisciplinary team was observed, developing and stimulating the evolution of low birth weight newborns in all clinical areas, whether in sensorimotor development, motricity, clinical stability, and transition of tube for exclusive breastfeeding, which brings long-term benefits to the nutritional development of the newborn. The profile of mothers and newborns stood out, where mothers who had greater family and team support were more likely to carry out the method, thus increasing exclusive breastfeeding rates, and cooperating with the clinical evolution of newborns of Low weight.